Philosophy of Science and the Challenges of Objectivity in the Use of AI in the Digital Age for Students - Giandra, Fauzi; Zein, Fariza Meydinatuz; Anjani, Mela (Maliki Interdisciplinary Journal, 2025)
This study examines the impact of artificial intelligence (AI) on student learning in the digital age, focusing on the challenges of objectivity in the philosophy of science. Using descriptive qualitative methods through a literature analysis of current literature sources, this study explores how AI facilitates personalized learning, time efficiency, and access to materials while accelerating data analysis in sciences such as biology and climatology. However, AI poses significant challenges, including diminishing critical thinking skills, creating algorithmic bias that repeats human stereotypes, and impacts of the digital age, such as the spread of unverified information through social media. Findings suggest that reliance on AI can undermine academic integrity and the objectivity of knowledge, encouraging plagiarism and a passive mindset. This study recommends the wise, ethical, and responsible use of AI, coupled with digital literacy, to uphold the principle of objectivity in the philosophy of science, thereby supporting students' intellectual development without replacing human thought.